A cost-effectiveness analysis of celecoxib compared with diclofenac in the treatment of pain in osteoarthritis (OA) within the Swedish health system using an adaptation of the NICE OA model. (September 2014) - Brereton, Nicholas; Pennington, Becky; Ekelund, Mats; Akehurst, Ronald
Abstract Objectives: Celecoxib for the treatment of pain resulting from osteoarthritis (OA) was reviewed by the Tandvårds- och läkemedelsförmånsverket–Dental and Pharmaceutical Benefits Board (TLV) in Sweden in late 2010. This study aimed to evaluate the incremental cost-effectiveness ratio (ICER) of celecoxib plus a proton pump inhibitor (PPI) compared to diclofenac plus a PPI in a Swedish setting. Methods: The National Institute for Health and Care Excellence (NICE) in the UK developed a health economic model as part of their 2008 assessment of treatments for OA. In this analysis, the model was reconstructed and adapted to a Swedish perspective. Drug costs were updated using the TLV database. Adverse event costs were calculated using the regional price list of Southern Sweden and the standard treatment guidelines from the county council of Stockholm. Costs for treating cardiovascular (CV) events were taken from the Swedish DRG codes and the literature. Results: Over a patient's lifetime treatment with celecoxib plus a PPI was associated with a quality-adjusted life year (QALY) gain of 0.006 per patient when compared to diclofenac plus a PPI. There was an increase in discounted costs of 529kr per patient, which resulted in an incremental cost-effectiveness ratio (ICER) of 82, 313kr ($12, 141). Sensitivity analysis showed that treatment was more cost effective in patients with an increased risk of bleeding or gastrointestinal (GI) complications. Conclusions: The results suggest that celecoxib plus a PPI is a cost effective treatment for OA when compared to diclofenac plus a PPI. Treatment is shown to be more cost effective in Sweden for patients with a high risk of bleeding or GI complications. It was in this population that the TLV gave a positive recommendation. There are known limitations on efficacy in the original NICE model.